Epiphytic algae on Norway spruce needles in Sweden - Poggio, Laura (2005)
The occurrence of epiphytic vegetation in temperate and boreal forest is a fairly recent phenomenon. Epiphytic algae have increased especially on Norway spruce (Picea abies L.Karst.) needles in the southern part of Scandinavia and in Central Europe. The algae present on spruce needles are mainly green algae and take their nutrients directly from rainwater and air. Thick layers of algae may accumulate over several years. The colonisation of the needles by the algae may cause different problems for the vitality of the tree. The most probable repercussion is the reduction of photosynthetic active irradiation available to the needles.